Maksud Tersembunyi dalam Tindak Tutur Ilokusi Film “Jembatan Pensil, Belajar pada Alam” Karya Hasto Broto - Mila Indah Rahmawati (Balai Bahasa Provinsi Riau, 2021)
Abstract The sense of speech can be different from the context of speech. There is also a need for further research using pragmatics. The purpose of this study was to identify the forms of Illocutionary Speech Analysis in the film